Pembelajaran Geometri melalui Aplikasi GLARE (Geometry Learning using Augmented Reality Experience) bagi Guru Matematika SMP - Auliya, Risma Nurul (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2025)
Mathematics is often considered one of the most challenging subjects because it requires strong spatial and cognitive abilities, especially in geometry, which involves three-dimensional concepts. Traditional teaching methods, such as textbook illustrations and verbal explanations, are often insufficient to help students understand abstract geometric concepts. The advancement of technology, particularly Augmented Reality (AR), offers innovative learning opportunities that combine real-world environments with digital content to enhance students’ understanding through interactive visualization. This community service activity aimed to explore teachers’ perceptions of using the GLARE (Geometry Learning using Augmented Reality Experience) application as a teaching aid in geometry learning. The program included training sessions, mentoring, and discussions with mathematics teachers at the secondary school level. The results showed that teachers had positive perceptions of using AR-based learning media, considering it effective in improving students’ conceptual understanding, engagement, and learning motivation. However, challenges remain regarding limited technical skills and school facilities for AR implementation. Overall, this program contributed to increasing teachers’ competence in integrating digital technology into mathematics education and promoting innovative, interactive, and technology-based learning approaches